2020
DOI: 10.1042/bsr20190987
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV attenuates high glucose-induced EMT by inhibiting the TGF-β/Smad pathway in renal proximal tubular epithelial cells

Abstract: In the present study, we examined the molecular mechanism of astragaloside IV (AS-IV) in high glucose (HG)-induced epithelial-to-mesenchymal transition (EMT) in renal proximal tubular epithelial cells (PTCs). NRK-52E cell viability and apoptosis were determined by the cell counting kit-8 (CCK-8) assay and flow cytometric analysis, respectively. Expressions of E-cadherin, N-cadherin, vimentin, and occludin were measured by Western blot, and those of E-cadherin and N-cadherin were additionally measured by immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
(44 reference statements)
2
19
1
Order By: Relevance
“…This protective effect has been observed in cardiomyocytes, renal tubular epithelial cells and retinal capillary endothelial cells exposed to high glucose. 4,26,27 In addition, these reports also show the anti-apoptotic and anti-oxidant properties of AS-IV. Similarly, in the current study, we also observed that through AS-IV treatment, cell apoptosis and oxidative stress originally induced by STZ have been alleviated to a certain extent.…”
Section: Discussionmentioning
confidence: 78%
“…This protective effect has been observed in cardiomyocytes, renal tubular epithelial cells and retinal capillary endothelial cells exposed to high glucose. 4,26,27 In addition, these reports also show the anti-apoptotic and anti-oxidant properties of AS-IV. Similarly, in the current study, we also observed that through AS-IV treatment, cell apoptosis and oxidative stress originally induced by STZ have been alleviated to a certain extent.…”
Section: Discussionmentioning
confidence: 78%
“…In agreement with this, our previous studies have reported that JPYSF notably reduced the increased levels of fibronectin and type IV collagen in renal fibrosis of 5/6 Nx rats ( Liu et al, 2018 ). Moreover, it has been reported that astragaloside IV up-regulates the decreased expressions of E-cadherin and occludin, whereas it down-regulates expressions of N-cadherin and vimentin in high glucose-induced EMT cells ( Wang YN et al, 2020 ). Therefore, we assume that JPYSF could regulate other epithelial markers and mesenchymal markers.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, A. mongholicus , A. macrocephala , D. oppositifolia , C. deserticola , A. kravanh , S. miltiorrhiza , R. palmatum , and G. uralensis were mixed in the ratio of 30:10:30:10:10:15:10:6. The detailed methods were as described previously ( Wang YN et al, 2020 ). The extract was freeze-dried and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, whether the TGF- β 1/Smad signaling pathway function is vital in inhibiting the invasion and metastasis of PLC and Huh7 cells by I-125 seed remains to be further studied. According to the past studies, TGF- β 1 activator can activate the TGF- β 1 signaling pathway, promote epithelial-mesenchymal transition, and then promote tumor invasion and metastasis [ 8 , 33 ]. Therefore, we studied the role of the TGF- β 1 activator in the inhibitory of the I-125 seed-induced cell migration.…”
Section: Discussionmentioning
confidence: 99%